Os mendigos de likes - Lima, Letícia Vargas de (2015)
The subject and its relation with the social ties, its behaviours and habits, are deeplly recreated facing the changes brought up by internet.Therefore, it has been an important researching field, given that its impacts to subjectivity are impossible to avoid. In this context, specially on Facebook, one may find a subject who spends most of its time on-line in its sui generis condition: beggars of likes. A subject who begs, tries to attract by image (not always his image), who bargains, who makes a marketing of itself to be. Beg for what? Likes, followers, friends, atention, popularity... beg for love. Turning the atention to this subject, this research aims generally to understand the pathos which works as a trigger for the daily battle of the beggars of likes in a social net, aiming to reach its targets. To enter the virtual environments of the beggars of likes, we use the etnographic method as a standard. We used the main instrument of the etnography, the field diary, and its excelence in exploring the stranger. The data analysis, as well as all the conception of the research, has been sustained by the Freudian psychoanalytic theory and some detailed concepts from Lacan. We also used the clinical position of the Fundamental Psychopathology, given that it bends towards the pathos, main objective of this research. From the life in the field, we extract elements which were splitted in three topics which will be better worked on: the beggar of likes , the Add game and Bruna França: to be or not to be a fake . An etymological approach between the words virtual/pulse and like/mock made it possible to discuss these subjects, leading to the place of the subject nowadays, specially on-line. We noticed that, under other clothing and new contexts, the unconscient subject, derived from the pulse, keeps on searching for ways to fulfill its structural emptiness, which always leads in frustration. Beggars of likes, thanks to the peculiarities of their acting field, soon meet this devastating pleasure which holds them to a repetition which defines their pathos and their condition.